Gender diversity, board monitoring and bank efficiency in ASEAN-5 - Ramly, Zulkufly; Chan, Sok-Gee; Mustapha, Mohd Zulkhairi; Sapiei, Noor Sharoja (Zes Rokman Resources, 2015)
We examine the effect of gender diversity and board monitoring (board size and independence) on bank efficiency. Using a broad panel of ASEAN-5 listed commercial banks over the period 1999-2012, we observe that gender diversity in bank board decreases cost and profit efficiency. This finding confirms our concern that the appointment of female directors in bank board is merely to comply with regulatory requirement and the market for high performing women directors could be limited, particularly in the banking sector. Our result also shows that board independence increases bank efficiency, suggesting that higher ratio of independent directors is related to the board ability to monitor and advise management; thus improving efficiency. However, we find that board independence confounded the negative effect of gender diversity on bank efficiency. This finding suggests that the inclusion of independent women directors in bank board fails to mitigate the negative effect of gender diversity on bank efficiency. Alternatively, the positive effect of an independent director towards monitoring and advisory roles of the board weakens if the director is a woman. Further, we find a U-shaped relation between board size and bank efficiency. Banks exhibit decreasing return to scale with small board size, and when the board size multiply the banks started to have better efficiency level. Our result casts doubt on most extant literature that asserts that one board size (either small or large) is always the way to go for all organizations.